Classification of optically trapped particles: A comparison between optical fiber tweezers and conventional setups - Pedro A.S. Jorge (Elsevier, 2021)
The classification of the type of trapped particles is a crucial task for an efficient integration of optical-tweezers in intelligent microfluidic devices. In the recent years, the use of the temporal scattering signal of the trapped particle paved for the use of versatile optical fiber solutions for performing such tasks, a feature previously unavailable as most methods required conventional optical tweezer setups. This work presents a comprehensive comparison of performances achieved with two distinct implementations – i)optical fiber and ii)conventional optical tweezers – for the classification of the material of particles through the analysis of the scattering signal with machine learning algorithms. The results suggest that while micron-sized particles can be accurately classified using the forward scattering information in conventional optical tweezers, when equipped with a quadrant photodetector, the optical fiber tweezers solutions can easily surpass its performance using the back-scattered information if the laser is modulated. Together with the advantages of being simpler, less expensive and more versatile, the results presented suggest that optical fiber solutions can become a valuable tool for miniaturization and integration of intelligent microfluidic devices working towards nanoscopic scales.